2020
DOI: 10.3390/pr9010025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blanching on Enzyme Inactivation, Physicochemical Attributes and Antioxidant Capacity of Hot-Air Dried Pomegranate (Punica granatum L.) Arils (cv. Wonderful)

Abstract: Blanch-assisted hot-air drying of pomegranate arils with blanching treatments 90 °C for 30 s, 100 °C for 60 s, and unblanched (control) arils were investigated. Effects of blanching on enzyme inactivation (polyphenol oxidase and peroxidse), colour, texture, and other qualities of dried arils were discussed. The hot-air drying conditions were 60 °C, 19.6% relative humidity, and 1.0 m s−1 air velocity. Results showed that blanching reduced enzyme activity by 76% and 68% for blanched arils treated at 90 °C for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…A calibrated CR-10 chromameter (Konica Minolta, Osaka, Japan) was used to measure the colour parameters yellowness (b∗), lightness (L∗), and redness (a∗) of the carrot slices during and after the drying period. According to Adetoro et al. (2021) , the total colour difference (ΔE) was calculated using Eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A calibrated CR-10 chromameter (Konica Minolta, Osaka, Japan) was used to measure the colour parameters yellowness (b∗), lightness (L∗), and redness (a∗) of the carrot slices during and after the drying period. According to Adetoro et al. (2021) , the total colour difference (ΔE) was calculated using Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The radical scavenging activity (RSA) of the carrot samples was determined using the 2.2-diphenylpicrylhydrazyl (DPPH) assay, according to Adetoro et al. (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…The stability of anthocyanin after the blanching process was also preserved by immediately cooling the samples in iced water to halt the heating process (Hadidi et al, 2019). Adetoro et al (2021) reported that blanching of dried pomegranate arils at 90°C for 30 s had the highest total anthocyanin content compared to blanching at 100°C for 60 s. Also, there was a study reported that dried slice of sweet purple potato steaming blanching at 70–80°C exhibited higher anthocyanin content (3.19 mg/g of cyanidin) compared to fresh purple sweet potato (2.84 mg/g of cyanidin), followed by blanching in hot water (2.19 mg/g of cyanidin) at 90–98°C (Mahmudatussa'Adah et al, 2019). This proved that blanching time should be considered since it may affect the loss of excessive anthocyanin compounds.…”
Section: Pretreatment Methods For Anthocyanin Extractionmentioning
confidence: 99%
“…However, at an increased drying temperature of 60 • C, the a* value decreased significantly to 10.09 ± 2.29 and approached the fresh samples; while at 80 • C, they increased again to 12.06 ± 2.26. The reason for this phenomenon might be related to the enzymatic and non-enzymatic browning of the fruits [32,33]. A higher a* value at 40 • C may be due to the enzymatic browning reactions that normally occur when the enzyme polyphenol oxidase (PPO) comes into contact with the endogenous phenolic compounds during mango drying.…”
Section: Color Changesmentioning
confidence: 99%